Clinicopathological investigations among recurrent camelpox outbreaks in Omanis’ Arabian camels (Camelus dromedarius) - Alkharusi, Amal; Al Khaldi, Nadia; Al-Sharji, Nada; Altoubi, Khalsa; Alsubhi, Taha; Al-Garadi, Maged A.; Al-Gabri, Naif; Ali, Haytham (Austral Journal of Veterinary Sciences, 2023)
Camelpox remains a widespread viral disease in camelids, with socioeconomic relevance. The present study explored the hematological, biochemical, and histopathological alterations in dromedary-racing camels from the North of Oman infected with camelpox virus diagnosed by real-time PCR. Blood and skin samples were collected from camels with clinical signs and skin lesions (n=4) and from healthy camels (n=3) from 10 different camel herds. The results indicated that the infected camels showed clinical signs, including pyrexia, lacrimation, nasal mucus discharge, affixed and swollen eyelids, emaciation, and pimples on the skin of the head, legs, and abdomen. Hemoglobin, hematocrit, and platelets were significantly greater, with a significant reduction in leukocyte and lymphocyte counts in infected camels than in healthy camels. Infected camels had higher CK and creatinine levels and hepatic-related metabolites, including AST, ALP, AST, GGT, and LDH, than the apparently healthy camels. Histopathological examination of skin scab samples revealed ballooning degeneration of epidermal cells in the presence of typical large eosinophilic intracytoplasmic inclusion bodies and suppurative dermatitis following secondary bacterial infection in all examined infected camels. Camelpox viral DNA was detected using real-time PCR in the blood and skin samples of all infected camels. These findings in dromedary-racing camels associated with a molecular diagnosis of camelpox are described for the first time in the Sultanate of Oman. Therefore, further studies are warranted.